Dough Mixer Machine Design Increases Cracker Production Capacity: Desain Mesin Pengaduk Adonan Meningkatkan Kapasitas Produksi Kerupuk - Muhammad Anggie Cahya Saputra; Mulyadi; A’rasy Fahruddin; Edi Widodo (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Productivity and consistency are essential factors in food processing industries, particularly in small and medium enterprises. Specific Background: Manual dough mixing in cracker production often results in low efficiency and inconsistent product quality. Knowledge Gap: Limited studies focus on practical machine design that addresses both productivity and consistency in small-scale cracker production. Aims: This study aims to design and develop a dough mixer machine to improve production capacity and mixing consistency. Results: The developed machine demonstrates improved mixing performance, increased production capacity, and more uniform dough compared to manual processes. Novelty: The study presents a practical machine design tailored for small-scale industries with specific capacity considerations. Implications: The results provide a reference for implementing appropriate technology to support productivity improvement in small-scale food production. Keywords: Dough Mixer, Machine Design, Productivity, Small Industry, Food Processing Key Findings Highlights Mechanical system enables higher output compared to manual mixing Process uniformity improves through controlled rotation mechanism Design supports small-scale production requirements